High-Yield Production of the Major Birch Pollen Allergen Bet v 1 With Allergen Immunogenicity in Nicotiana benthamiana - Yamada, Yuki; Kidoguchi, Masanori; Yata, Akira; Nakamura, Takako; Yoshida, Hideki; Kato, Yukinori; Masuko, Hironori; Hizawa, Nobuyuki; Fujieda, Shigeharu; Noguchi, Emiko; Miura, Kenji (Frontiers in Plant Science, 2020)
Type I allergy is an immunological disorder triggered by allergens and causes significant health problems. The major allergen of birch pollen is Bet v 1, which belongs to the pathogen-related protein 10 (PR-10) family. Here, we established a rapid and robust method for the production of Bet v 1 in Nicotiana benthamiana leaves, with binding activity to allergic patients’ IgE. The Bet v 1 allergen was expressed in N. benthamiana using a strong agroinfiltration-based transient protein expression system, which consists of a deconstructed geminiviral vector system with a double terminator. Five days post-infiltration, the allergen concentration in N. benthamiana leaves was 1.2 mg/g of fresh mass, being this the maximum yield of Bet v 1 in plants reported up to now. A part of plant-derived Bet v 1 was glycosylated. Bet v 1 purified from N. benthamiana or Brevibacillus brevis was used to carry out enzyme-linked immunoassays; both recombinant allergens were found to have comparable binding properties to the IgE of allergic patients. These results suggest that our plant expression system allows rapid and robust production of the allergen, which keeps the immunogenicity.